TEKNIK ASSERTIVE TRAINING DALAM PENDEKATAN BEHAVIORISTIK DAN APLIKASINYA KONSELING KELOMPOK: SEBUAH TINJAUAN KONSEPTUAL [ASSERTIVE TRAINING TECHNIQUES IN BEHAVIORISTIC APPROACHES AND ITS APPLICATIONS GROUP COUNSELING: A CONCEPTUAL REVIEW] - Azmi, Wifaqul; Nurjannah, N (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2022)
The purpose of this study was to describe assertive training techniques in the behavioristic approach and its application to group counseling. This research uses literature study method. The findings of the research are assertive training techniques are closely related to the behavioristic approach because the main purpose of assertive training is to convey well what is in the victim's heart, which causes discomfort so that it will have an impact on behavior change between these individuals. Assertive training techniques can be applied in group counseling which consists of three stages, namely the initial stage, the working stage, and the final stage.